Base-free and catalyst-free synthesis of functionalized dihydrobenzoxazoles via vinylogous carbonate to carbamate rearrangement - Das, Tamal Kanti; Mondal, Santigopal; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
An unexpected, catalyst-free, and base-free intramolecular cyclization of N-aryloxyacrylate aldimines, under thermal conditions leading to the synthesis of functionalized dihydrobenzoxazoles, is reported. The reaction features a unique rearrangement of vinylogous carbonates to vinylogous carbamates resulting in a new carbon–oxygen and carbon–nitrogen bond construction. The reaction tolerates a broad range of functional groups and the desired products are formed in moderate to good yields.

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Method for the analysis of free carbenes present after NHC-organocatalyzed transformations - Das, Tamal Kanti; Biju, Akkattu T. (European Journal of Organic Chemistry, 2017)
In N-heterocyclic carbene (NHC) based organocatalysis, usually, the free carbene is generated in situ by treatment of the azolium salt with a base. Described herein is a method for the analysis of the NHC present in the reaction flask after the NHC-organocatalyzed reaction. For this, the reaction mixture was treated with elemental sulfur after the reaction and the thus-formed thiourea/thione derivative was isolated. Common NHC-catalyzed transformations such as benzoin reactions, Stetter reactions, homoenolate annulation reactions, and reactions proceeding via the ,-unsaturated acylazolium intermediate have been studied. The results indicate that after the reactions, 28-84% of the initial carbenes exist in the free form.

N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.

N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis

Oxidative NHC catalysis for the generation of imidoyl azoliums: synthesis of benzoxazoles - Patra, Atanu; James, Anjima; Das, Tamal Kanti; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
N-Fleterocyclic carbene (NHC)-catalyzed intramolecular cyclization of aldimines generated from 2-amino phenols and aromatic aldehydes leading to the synthesis of 2-arylbenzoxazoles under mild conditions is presented. The reaction proceeds via the generation of the aza-Breslow intermediates from imines and NHC, which under oxidative conditions form the key imidoyl azoliums and a subsequent intramolecular cyclization furnishes the product. The reaction tolerates a broad range of functional groups, and the products are formed in generally good yields.

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Imines as acceptors and donors in N-heterocyclic carbene (NHC) organocatalysis - Das, Tamal Kanti; Biju, Akkattu T. (Chemical Communications, 2020)
The synthetic potential of imines as electrophiles or as a source of nucleophilic coupling partner in N-heterocyclic carbene (NHC) catalysis for the synthesis of various nitrogen heterocycles and functionalized amines is highlighted in this Feature Article. Electrophilic imines are suitable candidates for intercepting the NHC-derived acyl anions, homoenolate equivalents, and (di)enolates for the synthesis of alpha-amino ketones and a variety of lactam derivatives. Moreover, enamines generated from imines bearing alpha-hydrogen could be trapped with alpha,beta-unsaturated acylazoliums for the synthesis of functionalized dihydropyridinones. NHCs are also useful for the umpolung of imines for the generation of aza-Breslow intermediates thus leading to the synthesis of indoles, quinolines, dihydroquinoxalinesetc.A concise account of the diverse reactivity of imines in NHC catalysis has been presented.

N-heterocyclic carbene catalysis exploiting oxidative imine umpolung for the generation of imidoyl azoliums - Das, Tamal Kanti; Madica, Krishnaprasad; Krishnan, Jagadeesh; Marelli, Udaya Kiran; Biju, Akkattu T. (Journal of Organic Chemistry, 2020)
Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cyclization and preliminary mechanistic experiments are also provided.

N-heterocyclic carbene (NHC)-catalyzed transformations for the synthesis of heterocycles - Das, Tamal Kanti; Biju, Akkattu T. (Progress in Heterocyclic Chemistry, 2020)
N-heterocyclic carbene (NHC)-based organocatalysis has been widely used for unconventional access to various target molecules. The use of chiral NHCs in the process results in the enantioselective synthesis of various heterocycles. The underlying principle of many of the NHC-catalyzed reactions is the remarkable ability of NHCs to reverse the normal mode of reactivity of aldehydes (umpolung). NHCs can catalyze transformations proceeding via the umpolung or nonumpolung mode for the synthesis of various functionalized molecules. The recent advances in the application of NHCs for the synthesis of various heterocyclic compounds are highlighted in this chapter.
Keywords: aldehyde umpolung; Aldimine umpolung; benzoin reaction; Breslow intermediates; Enantioselective synthesis; Heterocyclic synthesis; N-Heterocyclic carbene; Stetter reaction